2019
DOI: 10.1111/bjh.15797
|View full text |Cite
|
Sign up to set email alerts
|

Combination lenalidomide‐rituximab immunotherapy activates anti‐tumour immunity and induces tumour cell death by complementary mechanisms of action in follicular lymphoma

Abstract: Summary Chemotherapy plus rituximab has been the mainstay of treatment for follicular lymphoma ( FL ) for two decades but is associated with immunosuppression and relapse. In phase 2 studies, lenalidomide combined with rituximab (R 2 ) has shown clinical synergy in front‐line and relapsed/refractory FL . Here, we show that lenalidomide reactivated dysfunctional T and Natural Killer ( NK ) cells ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 43 publications
0
27
0
1
Order By: Relevance
“…We substantiate the selective influence of this immunomodulatory agent to potentially restore this immune synapsis, corroborating in vitro and in vivo experiments in different settings of haematological diseases (Gorgun et al , ; Balaian et al , ; Grygorowicz et al , ). Along these lines, using samples of the RELEVANCE trial, Chiu et al , () could demonstrate by analysis of peripheral blood patient samples and in vitro that lenalidomide can reactivate anergic/silenced natural killer (NK) cells and T cells and that patients receiving R 2 therapy had higher circulating amounts of T and NK cells in comparison to patients of the R arm (Chiu et al , ). Lenalidomide was shown to be capable of (re)activating the interaction of these T and NK cells with lymphoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…We substantiate the selective influence of this immunomodulatory agent to potentially restore this immune synapsis, corroborating in vitro and in vivo experiments in different settings of haematological diseases (Gorgun et al , ; Balaian et al , ; Grygorowicz et al , ). Along these lines, using samples of the RELEVANCE trial, Chiu et al , () could demonstrate by analysis of peripheral blood patient samples and in vitro that lenalidomide can reactivate anergic/silenced natural killer (NK) cells and T cells and that patients receiving R 2 therapy had higher circulating amounts of T and NK cells in comparison to patients of the R arm (Chiu et al , ). Lenalidomide was shown to be capable of (re)activating the interaction of these T and NK cells with lymphoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The 5/7-day schedule was introduced based on preclinical data from an in vitro assay of neutrophil differentiation. 52 In these experiments, continuous treatment of bone marrow precursor cells with avadomide led to an arrest in myeloid maturation at a promyelocyte stage with a 90% decrease in mature neutrophil counts compared with vehicle control (supplemental Figure 4). Shifting to a 5/7-day treatment schedule partially relieved the arrest and allowed mature neutrophil populations in the cultures to expand.…”
Section: Avadomide Treatment Alters Peripheral T-cell Phenotypes and mentioning
confidence: 76%
“…We recently reported that lenalidomide-mediated degradation of Ikaros in an in vitro model of myeloid differentiation results in a reversible arrest in neutrophil maturation, which is released upon removal of the drug, without any loss of cell viability. 52 Using a similar preclinical model, we demonstrated that treatment of human bone marrow precursor cells with avadomide on a novel 5/7-day schedule allowed Ikaros to be resynthesized during the 2-day drug holiday, enabling mature neutrophils to repopulate after a transient arrest. 57 Our data demonstrate the potent immunomodulatory activity of avadomide, including positive effects on T-cell activation and a broad expansion of T-cell populations, as defined by an increase in richness of the peripheral T-cell repertoire.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, lenalidomide markedly increases NK cell activation and proliferation through the induction of IL-2 production by CD4 T cells in chronic lymphocytic leukemia (CLL) [46,47]. Also, lenalidomide increases NK cell numbers, promotes the expression of activating receptors, such as CD16, and reduces that of checkpoint receptors, thus enhancing NK cell-mediated cytotoxicity and ADCC [45,46,[48][49][50]. Moreover, lenalidomide increases the expression of NKG2D and DNAM-1 ligands (MICA and PVR) in multiple myeloma [51].…”
Section: Nk Cell-based Therapiesmentioning
confidence: 99%